THEORETICAL AND APPLIED ASPECTS OF CONTRASTIVE LINGUISTICS - Khudoynazarova Uglonoy Allamurodovna (Western European Studies, 2025)
This article explores the historical development, theoretical foundations, and applied dimensions of contrastive linguistics. It analyzes the relationship between contrastive and comparative linguistics, discusses macro- and micro-contrastive approaches, and highlights the distinction between theoretical and applied contrastive studies. The importance of contrastive linguistics in language teaching, translation studies, and intercultural communication is emphasized.
Keywords: contrastive linguistics; comparative linguistics; tertium comparationis